The Effects of Rate Regulation on the Volatility of Auto Insurance Prices - Evidence from Canada - Leadbetter, Darrell; Voll, Jane; Wieder, Erica (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2008)
Previous studies using U.S. data have found that rate regulation reduces competition, availability of coverage and increases volatility of insurance premiums. This article extends the U.S. literature to the Canadian context to examine whether rate regulation increases premium volatility in the province of Ontario. Based on an empirical analysis using data covering six provinces over the 18–year period from 1984 to 2001 we find that rate regulation is significant in explaining the volatility in average insurance premiums, after accounting for claims related costs. This finding is consistent with results from other jurisdictions.